A novel truncating mutation in MYH3 causes spondylocarpotarsal synostosis syndrome with basilar invagination. Issue 12 (December 2018) - Takagi, Masaki; Shimomura, Satoshi; Fukuzawa, Ryuji; Narumi, Satoshi; Nishimura, Gen; Hasegawa, Tomonobu
Abstract Spondylocarpotarsal synostosis syndrome (SCT) is a rare group of skeletal dysplasias, characterized by disproportionate short stature with a short trunk, abnormal segmentation of the spine with vertebral fusion, scoliosis and lordosis, carpal and tarsal synostosis, and mild facial dysmorphisms. While the majority of the cases show autosomal recessive inheritance, only a few cases of vertical transmissions, withMYH3 mutations, have been reported. Here we report a case with typical SCT, carrying a novel heterozygous mutation inMYH3 . This observation supports the hypothesis of a pathogenic link between autosomal dominant SCT and heterozygous mutations inMYH3 . Of note, our case showed basilar invagination on brain magnetic resonance imaging at the age of 10 years. Basilar invagination could be a rare complication of both autosomal recessive and dominant SCT, indicating that prompt investigation are warranted for SCT patients.